Improving Teacher Professional Development Through Social Media Optimization Training in Project-Based Learning in Work Education and Entrepreneurship - Diyah Candra Arifah, Ika; Kholidi Hadi, Hafid; Kharisma, Fresha; Purwohandoko, Purwohandoko (International Journal of Community Service Learning, 2023)
Entrepreneurship education is very important to implement in order to prepare students to have entrepreneurial life skills that are creative, courageous, trained to become advanced individuals, and have a better quality of life. However, not all teachers understand the role of social media for marketing in increasing the engagement of prospective buyers, influencing consumer behavior and increasing sales of student work. The purpose of implementing this community service activity is to provide training on optimizing social media in project-based learning with local content, craft and entrepreneurship education for teachers. The method used in community service is in the form of integrated training which begins with the provision of material related to social media and Project-Based Learning to teachers. The target in this community service activity is 36 teachers at SMA. This community service shows good results with an increased understanding of social media marketing and training in the use of social media that is effective enough to provide technical skills in using social media in entrepreneurship subjects.